Impact of a residential rural community-based training program for medical students on cognitive and affective domains of learning in community medicine: A mixed methods study - Farah Naaz Fathima; Avita Rose Johnson; Pretesh Rohan Kiran; S Ratnakumari; Bobby Joseph (Wolters Kluwer Medknow Publications, 2021)
Introduction: As part of undergraduate training in community medicine, students of 1st-year MBBS at our medical college in South India undergo rural residential community-based training called Rural Orientation Program (ROP). Objective: The objective was to study the impact of ROP at a medical college in South India. Methodology: Short-term impact was studied immediately before and after ROP using a 30-item questionnaire administered to 142 students. Medium-term impact was studied among 23 students in 2nd-year MBBS. Quantitative component consisted of objective structured practical examination scores and qualitative component documented reflections on learnings. Long-term impact was studied by surveying 287 alumni (batches of 1979 onward) to explore the impact of ROP on their career. Results: We found a significant (P < 0.001) improvement in the median posttest score (21, interquartile range [IQR]: 20-23) when compared to pretest (12, IQR: 10-16). The mean OSPE score was 19.34 ± 3.19 (maximum score = 25) with 54.55% obtaining a score ≥20. Thematic analysis of reflections depicted that students gained insights on factors influencing health and social organizations in rural areas. ROP helped develop empathy toward patients and a holistic approach toward health, in understanding rural dynamics and improved communication skills. Conclusion: ROP increases subject knowledge and plays a role in molding attitudes of students toward the care of people in rural areas and improves communication skills. This time-tested model can be replicated in other medical colleges across the country.